FLIPPED LEARNING IN ENGLISH AS A FOREIGN LANGUAGE CLASSROOMS: ENHANCING STUDENT ENGAGEMENT AND LANGUAGE ACHIEVEMENT - Dilfuza Shuxratovna; Yusufjanova Muattar Baxrom qizi (TADQIQOTLAR, 2026)
Abstract The rapid development of educational technology has significantly influenced the field of foreign language teaching, leading to the emergence of innovative pedagogical approaches that promote active learning and learner autonomy. Among these approaches, flipped learning has gained increasing attention due to its ability to reverse traditional instructional practices by delivering content outside the classroom and dedicating classroom time to collaborative and communicative activities. This paper examines the role of flipped learning in English as a Foreign Language (EFL) education and explores its impact on student engagement and language achievement. It argues that the effectiveness of flipped learning depends on the successful integration of digital resources, pedagogical planning, and learner participation. While the approach offers numerous benefits, including increased interaction, flexibility, and autonomy, challenges related to technological access and learner readiness remain. Ultimately, flipped learning should be viewed as a complementary instructional model that enhances, rather than replaces, traditional language teaching practices.